Creation of a Mixed‐Mode Fracture Network at Mesoscale Through Hydraulic Fracturing and Shear Stimulation. Issue 12 (18th December 2020) - Schoenball, Martin; Ajo‐Franklin, Jonathan B.; Blankenship, Doug; Chai, Chengping; Chakravarty, Aditya; Dobson, Patrick; Hopp, Chet; Kneafsey, Timothy; Knox, Hunter A.; Maceira, Monica; Robertson, Michelle C.; Sprinkle, Parker; et al.
Abstract: Enhanced Geothermal Systems could provide a substantial contribution to the global energy demand if their implementation could overcome inherent challenges. Examples are insufficient created permeability, early thermal breakthrough, and unacceptable induced seismicity. Here we report on the seismic response of a mesoscale hydraulic fracturing experiment performed at 1.5‐km depth at the Sanford Underground Research Facility. We have measured the seismic activity by utilizing a 100‐kHz, continuous seismic monitoring system deployed in six 60‐m length monitoring boreholes surrounding the experimental domain in 3‐D. The achieved location uncertainty was on the order of 1 m and limited by the signal‐to‐noise ratio of detected events. These uncertainties were corroborated by detections of fracture intersections at the monitoring boreholes. Three intervals of the dedicated injection borehole were hydraulically stimulated by water injection at pressures up to 33 MPa and flow rates up to 5 L/min. We located 1, 933 seismic events during several injection periods. The recorded seismicity delineates a complex fracture network comprised of multistrand hydraulic fractures and shear‐reactivated, preexisting planes of weakness that grew unilaterally from the point of initiation. We find that heterogeneity of stress dictates the seismic outcome of hydraulic stimulations, even when relying on theoretically well‐behaved hydraulic fractures. Once hydraulic fractures intersected boreholes, the boreholes acted as a pressure relief and fracture propagation ceased. In order to create an efficient subsurface heat exchanger, production boreholes should not be drilled before the end of hydraulic stimulations. Key Points: Mesoscale hydraulic fracturing in crystalline rock is observed with multigeophysical sensor array at close proximity Created fracture network consists of multistrand hydraulic fractures and reactivated preexisting structures Hydraulic fracture growth is strongly influenced by rock fabric, preexisting fractures, and stress heterogeneities